2023
DOI: 10.1002/fsn3.3403
|View full text |Cite
|
Sign up to set email alerts
|

Formula feeding and associated factors among mothers with infants 0–6 months old in Mettu Town, Southwest Ethiopia

Abstract: Adequate nutrition during infancy is essential for children's normal development and well-being. However, the duration of breastfeeding has been declining and is being replaced by formula feeding, particularly in the urban communities of developing countries, including Ethiopia. Hence, this study aimed to assess formula feeding and its associated factors, as relatively little information is available regarding this problem in Ethiopia, particularly in Mettu Town. A community-based cross-sectional study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Our study also demonstrated that mothers who had not initiated breastfeeding within one hour of delivery were approximately five times more likely to practice infant formula feeding than were those who had initiated breastfeeding within one hour of delivery. This result is in agreement with the results of studies conducted in Addis Ababa city, Mettu town, and Bahir Dar city [39,41,42]. A possible justification might be that early initiation of breastfeeding fosters a strong bond between the mother and her baby, and such a strong relationship can lay the groundwork for mothers to spend more time with their babies and breastfeed them promptly.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our study also demonstrated that mothers who had not initiated breastfeeding within one hour of delivery were approximately five times more likely to practice infant formula feeding than were those who had initiated breastfeeding within one hour of delivery. This result is in agreement with the results of studies conducted in Addis Ababa city, Mettu town, and Bahir Dar city [39,41,42]. A possible justification might be that early initiation of breastfeeding fosters a strong bond between the mother and her baby, and such a strong relationship can lay the groundwork for mothers to spend more time with their babies and breastfeed them promptly.…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of infant formula-fed infants in Debre Berhan city was higher than that in Offa town (7.8%), Mettu town (28.4%), and Bahir Dar city (25%) [39,40,42]. In contrast, it was lower than the level found in Dire Dawa city (42.6%), Addis Ababa city (46.2%), and the Jimma Zone (47.2%) [41,44,45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations